Intraperitoneal Injection of High Tumor Necrosis Factor (TNF-Î±) Serum Increase Soluble Fms-like Tyrosine Kinase-1 (sFlt-1) and Blood Pressure of Pregnant Mice - Bramantyo Aji Wicaksono; Siti Candra Windu Baktiyani; Loeki Enggar Fitri (Journal of Tropical Life Science, 2015)
Preeclampsia has major symptoms of hypertension and proteinuria and is a cause of significant maternal and infant mortality in the world. The slow development of preeclampsia research possibility caused by the difficulty in acquiring animal preeclampsia. Many existing animal model have been developed, but most of them are expensive to do. The purpose of this study was to determine the effects of intraperitoneal injection of pregnant patients serum with high TNF-Î± levels toward sFlt-1 serum concentration and blood pressure of pregnant mice. Pregnant patients serum with high TNF-Î± levels (>20 pg/mL) was injected intraperitoneally to pregnant mice at gestational age 13 and 14 days. At 18 days of gestation, the blood pressure was measured, then the mice were dissected and the serum was taken to measure serum sFlt-1 concentration using ELISA kit(Bioassay Technology Laboratory, E0611Mo). The results showed there was a significant increase in blood pressure (p = 0.000) and the sFlt-1 levels (p = 0.002) of pregnant mice group that injected by pregnant patient serum with high TNF-Î± levels compare to control group. From these data it can be concluded that intraperitoneal injection of pregnant patients serum with high TNF-Î± levels to pregnant mice can increase blood pressure and sFlt-1 serum concentration of mice.